2011
DOI: 10.1016/j.actatropica.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Acanthamoeba spp. from air-conditioners in Kuala Lumpur, Malaysia

Abstract: During a study on the quality of the indoor environment, Acanthamoeba spp. were detected in 20 out of 87 dust samples collected from air-conditioners installed in a four-story campus building located in Kuala Lumpur, Malaysia. Twenty-one cloned Acanthamoeba isolates designated as IMU1 to IMU21 were established from the positive primary cultures. Five species were identified from the 16 isolates according to the morphological criteria of Pussard and Pons; i.e. A. castellanii, A. culbertsoni, A. griffini, A. hat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 42 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…However, these earlier studies focused on only a single ophthalmology hospital and analyzed five dust samples of ophthalmology wards, which contained the Acanthamoeba T4 genotype (Niyyati et al 2009a). The present study was a comprehensive survey with 70 samples and also included biofilms as a potential source of proliferation of FLA. Airborne dust, combined with high levels of air pollution, is frequent in Tehran, enabling cysts to be transferred by visitors from outside to the indoor environment of hospital wards (Teixeira et al 2009;Chan et al 2011;Costa et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these earlier studies focused on only a single ophthalmology hospital and analyzed five dust samples of ophthalmology wards, which contained the Acanthamoeba T4 genotype (Niyyati et al 2009a). The present study was a comprehensive survey with 70 samples and also included biofilms as a potential source of proliferation of FLA. Airborne dust, combined with high levels of air pollution, is frequent in Tehran, enabling cysts to be transferred by visitors from outside to the indoor environment of hospital wards (Teixeira et al 2009;Chan et al 2011;Costa et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of FLA was confirmed from cyst and trophozoite morphology (Page 1988). For further evaluation and for elimination of bacterial and fungal contamination as well as to avoid phagocytosis of target amoebae by Thecamoeba, the cysts were cloned (Chan et al 2011), and subcultured by cutting out a small piece of agar and placing it onto a fresh plate.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to mention, Iran is a country with large amounts of dust in the environment that would allow the amoebae to resist to harsh conditions in their dormant cyst stage and spread them in the environment easily (Niyyati et al 2009b). There are only a few reports on the isolation of FLA from dust and biofilms (Chan et al 2011;Zegans et Lasjerdi et al 418 2002). However a recent study in the city of Tehran reported the presence of FLA belonging to Acanthamoeba genus and also Balamuthia mandrillaris was isolated from a dust sample in this region (Niyyati et al 2009c).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally they have been reported to be isolated from human-made environments such as drinking water, bottled spring water, distilled water in laboratories, chlorinated swimming pools and contact lens storage cases. [23][24][25][26] Granulamatous amoebic encephalitis (GAE) cases are commonly detected to involve Acanthamoeba culbertsoni, A. castellanii and A. rhysoides species. Acanthamoeba keratitis is a parasitosis caused by a variety of Acanthamoeba species.…”
Section: 20mentioning
confidence: 99%